Memorandum of Understanding between the International Livestock Research Institute (ILRI) and Arsi University - International Livestock Research Institute; Arsi University (2021)
Memorandum of understanding (MOU) between the International Livestock Research Institute (ILRI) and Arsi University. MOU signed on December 23, 2021 by Jimmy Smith, Director-General of ILRI and Duguma Adugna, President of Arsi University.